HUBUNGAN MINAT DAN MOTIVASI MENJADI BIDAN TERHADAP PRESTASI BELAJAR MAHASISWA D-III KEBIDANAN SEMESTER II DAN IV UNIVERSITAS BATAM TAHUN 2017 - Masyitha, Cahyaa; Yunita, Prasida (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
To become an eligible professional, one must with impeccable and drive towards greatmess, withal, the statistics has reported that the number of srudents enrollment majoring in midwifery in health-study institution keeps decreasing each year running the very same study program are visibly available and making them in the competition to enroll as many new students as possible. One scholl of midwifery academic in Tangerang for instance, reportedly had 72 students enrolled in 2012, slumped to 43 students enrolled by 2014. In the Batam University, from 42 students enrolled in 2013 declined to 24 students in 2016. This research aims to discover the impact of personal passion and pursuit becoming a midwifery on the Grade Point Averages (GPAs) of the second and the fouth-semester students of D-III Midwifery of the Batam University in 2017. The research method analytic cross-sectional design. The population was the second-and the fourth-semester students with the total of 62 respondents as the sample. On the research on investigating the correlation of the students’ pursuit becoming a midwife on their GPAs, the chi-square test result reveal p value = 0.015 (<0,05). While in the reflective context of the sorrelation of the students’ passion to become a midwife on their GPAs, the chi-square test result reveals p value = 0,003(<0,05). In suggestion, health-study institution the Batam University specifically should improving and monitoring their education quality, to a better promotion.